9t=-10t-3

Simple and best practice solution for 9t=-10t-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9t=-10t-3 equation:


Simplifying
9t = -10t + -3

Reorder the terms:
9t = -3 + -10t

Solving
9t = -3 + -10t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '10t' to each side of the equation.
9t + 10t = -3 + -10t + 10t

Combine like terms: 9t + 10t = 19t
19t = -3 + -10t + 10t

Combine like terms: -10t + 10t = 0
19t = -3 + 0
19t = -3

Divide each side by '19'.
t = -0.1578947368

Simplifying
t = -0.1578947368

See similar equations:

| -5(2x-9)=2(x-8)11 | | 20x^3+8x^2+12x= | | 4-18=z/-9 | | 12x-8=11x | | 2x^2+8x+6=8 | | 9w-8w+2=-4+2w | | 3/4c=72 | | 5j-440=30 | | 3D-10=6-5d | | -3(x-4)=-1 | | 10+c-8c=-10-3c | | 8x+12=-6x-16 | | -6(2)(-1)(-1)= | | y=niga | | 0=x^2-192X+1080 | | 6-3z=-5z-8 | | g^2-2g-8= | | 7-7q=-2q-8 | | 5y+1.5=2y-4 | | 6x+13=-5x-18 | | -9+9p=10p | | -4j+9=-3j | | 2(x+6)+3=5x-7 | | (3x+38)=5x | | 3x+14=-5x-17 | | 3x^9+39x^8+108x^7=0 | | 5-w=-16 | | 7x+10=-5x-16 | | 6x+6+2y=66 | | -5[x+6]=-5x+9 | | 12-21=-9 | | 3-6+2-1+8= |

Equations solver categories